Morphological variation of Hoya multiflora Blume at different habitat type of Bodogol Research Station of Gunung Gede Pangrango National Park, Indonesia - SRI RAHAYU; MUHAMMAD JUSUF; SUHARSONO SUHARSONO; CECEP KUSMANA; ROCHADI ABDULHADI (Society for Indonesian Biodiversity, 2010)
Rahayu S, Jusuf M, Suharsono, Kusmana C, Abdulhadi R. (2010) Morphological variation of Hoya multiflora Blume at different habitat type of Bodogol Research Station of Gunung Gede Pangrango Natonal Park, Indonesia. Biodiversitas 11: 187-193. Hoya multiflora Blume (Asclepiadaceae) is an Asiatic tropical epiphytic shrub which has been utilized as ornamental plant and reported to possess medicinal properties. The aim of this study was to evaluate the morphological variation of Hoya multiflora populations at the different habitat types of Bodogol Research Station of Gunung Gede Pangrango National Park in Indonesia. We collected 48 samples from three sub populations with six different habitat types. Morphological variation was found in stem, leave, and inflorescence. According to thediscriminant and cluster analysis, the 48 samples were separated into three groups at 12% dissimilarity. The groups were determined by canopy cover degree.Key words: morphological diversity, Hoya multiflora, Gunung Gede Pangrango National Park